The second disestablishment: church and state in nineteenth-century America - Green, Steven K. (Oxford University Press, 2010)
Study of the relationship between church & state in America tends to focus either on the founding period or the modern era. Steven Green argues that a crucial development occurred during the 19th century as legal & educational reforms & a growing appreciation of the nation's religious diversity led to a second disestablishment